Flow rate variance of a fully implantable pump for the delivery of intravenous treprostinil in pulmonary arterial hypertension. (March 2020) - Richter, Manuel J.; Harutyunova, Satenik; Bollmann, Tom; Classen, Simon; Fuge, Jan; Gall, Henning; Gerhardt, Felix; Ghofrani, Hossein A.; Gunkel, Hartmut; Grünig, Ekkehard; Halank, Michael; Heine, Alexander; et al.
Implantable infusion pumps might improve the convenience and safety of intravenous treprostinil for pulmonary arterial hypertension. The LENUS Pro® pump (approved in Europe) has a fixed flow rate. Based on 126 pumps and 2853 refills, we retrospectively analyzed the actual flow rate from 09/2010 to 09/2018. A relevant flow rate variance is evident after three years; therefore, flow rate monitoring and dose adjustment are mandatory.